2020
DOI: 10.1093/ofid/ofaa646
|View full text |Cite
|
Sign up to set email alerts
|

Mucormycosis in Hematopoietic Cell Transplant Recipients and in Patients With Hematological Malignancies in the Era of New Antifungal Agents

Abstract: Background The survival benefit of combination antifungal therapy for invasive mucormycosis (IM) in patients with hematologic malignancy (HM) and hematopoietic cell transplant (HCT) is not well defined. Methods This multicenter, retrospective study included HM and HCT recipients with proven or probable IM between January 1, 2007 and December 31, 2017 from 10 transplant centers across North America. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 20 publications
1
18
0
1
Order By: Relevance
“…A prompt diagnosis and treatment should be established because of the angioinvasive character and rapid disease progression leading to a high mortality. 48 , 49 This is especially true in India; with an increased incidence of COVID-19 cases, apparently thousands of CAM cases are reported. However, Nepal, Brazil, Colombia, the USA, and other severely affected nations should consider this fungal threat amid the pandemic.…”
mentioning
confidence: 99%
“…A prompt diagnosis and treatment should be established because of the angioinvasive character and rapid disease progression leading to a high mortality. 48 , 49 This is especially true in India; with an increased incidence of COVID-19 cases, apparently thousands of CAM cases are reported. However, Nepal, Brazil, Colombia, the USA, and other severely affected nations should consider this fungal threat amid the pandemic.…”
mentioning
confidence: 99%
“…Although our study did not show empirical antifungal treatment before the diagnosis of mucormycosis causing increased mortality limited by the number of cases, breakthrough infection still remains a serious issue in fungal infection after allo-HSCT. A recent study indicated that the overall prognosis in HSCT and HM populations remains extremely poor after diagnosis, with only a 37% survival rate at 1 year [ 39 ]. In our cases, the survival rate at 1 year is 28.6%.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, b-IFI following voriconazole prophylaxis has been reported in up to 7.9% of cases, primarily mucormycosis, due to the lack of in vitro activity against Mucorales [ 4 ]. Mucormycosis, including Rhizopus microsporus , mainly affects immunocompromised hosts and, after IA, represents the most frequent IFI in hematological patients and HSCT recipients [ 22 , 23 , 24 , 25 ]. Mucormycoses are characterized by rapid local spread, angioinvasion and tissue necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Most common presentations are rhino-orbito-cerebral, cutaneous, pulmonary and disseminated, the latter two being more frequent among neutropenic patients with acute leukemia and HSCT recipients. The latter two are also associated with high mortality rates (20–100%) [ 22 , 23 , 25 , 26 ]. The ESCMID-ECCM and ECIL-6 guidelines recommend surgery and first-line treatment with L-AMB at least 5 mg/kg/day.…”
Section: Discussionmentioning
confidence: 99%